Educação infantil e participação: um estudo das representações sociais de pais de uma escola pública municipal de Belém - FERREIRA, Heloiza do Socorro Nóbrega (Universidade Federal do Pará, 2011)
This work deals with the Social Representations and Infantile Education. It analyzes the parents' social Representations about their Infantile Education and participation in the Education of the children who study at public schools in the Belém's municipal net. It was based on the theoreticalmethodological referential of the Social Representations with bases on Moscovici (1978, 2003), Lefevre (2005), Jodelet (2001) and theoricists who study the childhood, infantile education and participation, such as Ariès (1981), Kramer (1984, 2003), Kuhlmann (2004), Sarmento (2001), Paro (2000), Lima (2008). The study is a research of the descriptive type. It had as instrument of data collection, questionnaires, images and focal group, in which participated mothers, grandmother and father (totaling twelve subjects), who had their children in the infantile education of a school of the municipal public net in the year of 2007. The results of the study reveal that the parents possess information about the Infantile Education with emphasis in the learning process and socialization. They believe that the infantile education will subsidize the success for the whole education of the children and consequently a professional future. The parents' social representations about their participation in the children's education are materialized in attendances to school meetings, orientation towards the school guidances and the dialogue with the professionals. In such a process of representations of participation, conducts of sharing are anchored for some, and for other parents, of listening, silence, reservedly shared to question the work developed by the school, having in mind that parents cultivate faiths and idealizations due to the school education and the authority that they realize in the professionals who educate their children. The dialogue with the parents demonstrated that this relationship is not free of conflicts or dissatisfactions. In our final considerations, elements that can contribute to the promotion of the parents' participation in the Infantile Education are pointed out.